Ethnomathematics Identification in West Sumatra Rantak Dance Performances - Yusnizar, Yusnizar; Yahfizham, Yahfizham (Universitas Negeri Semarang, 2024)
The diversity of traditional dance performances in Indonesia showcases the country's rich cultural heritage. The art of Rantak dance from West Sumatra, Indonesia, is one such cultural treasure that exhibits connections with ethnomathematics. This research aims to explore the relationship between culture and mathematics education in schools by identifying aspects of the Rantak dance. The research method employed was qualitative descriptive using an ethnographic approach. Data analysis techniques follow Miles and Huberman's approach, involving data reduction, data display, and drawing conclusions. The findings of this research reveal a significant correlation between the cultural art of Rantak dance from West Sumatra and mathematics. This connection is observed in the floor patterns that form geometric shapes such as triangles and circles. Additionally, the formation of straight lines at 180° is evident within the dance. The musical instruments accompanying the dance also feature mathematical elements, such as the cylindrical shape of the